Application of three dimensional electromechanical impedance model for damage assessment of plate - Annamdas Venu Gopal Madhav (2013)
Cost-effective and reliable damage detection models are crucial for successful monitoring of any ancient or modern age engineering structure. Lead Zirconate Titanate (PZT) based electromechanical impedance (EMI) method is emerging as a promising alternate for conventional structural health monitoring (SHM) of various engineering structures. The PZT patches are usually surface bonded and then excited in the presence of electric field to a desired frequency spectrum. The excitations result in prediction of unique frequency dependent electromechanical (EM) admittance signature. Any change in the signature during the monitoring period indicates dis-integrity/ damage in the host structure. However, apart from locating damages, the increase in severity of damages has to be predicted on time to avoid collapse of the entire structure. This paper presents such a model which had effectively predicted the severity of damages along a principle direction of the structure. This was achieved by experimental damage study on plates and subsequent verification by semi numerical 3D model. Statistical root mean square deviation (RMSD) index was used for evaluating the damages made on plates. Additionally, a new frequency proximity index (FPI) was introduced to measure the effectiveness of the model. RMSD measures the changes in height of peaks of signature and FPI scales the frequency spectrum of signature. Thus results of RMSD index and FPI are used as complementary to each other to study damage propagation in a structure.